Dual-encryption based on facilely synthesized supra-(carbon nanodots) with water-induced enhanced luminescence. Issue 83 (22nd August 2016) - Zhang, Xutao; Li, Di; Zhou, Ding; Jing, Pengtao; Ji, Wenyu; Shen, Dezhen; Qu, Songnan
Abstract : Dual-encrypted luminescence information has been constructed through water-jet printing and hand writing based on low cost and easily prepared supra-(carbon nanodots). Abstract : A series of low cost and easily prepared supra-(carbon nanodots (CNDs)) were developed by injecting CND ethanol solutions into toluene under vigorous stirring to induce nano-sized aggregates. Water-jet printing of luminescent patterns and mapping of human sweat pore patterns can be realized on the supra-CND-coated paper. With the application of two kinds of supra-CNDs, dual-encrypted luminescence information was constructed through water-jet printing and hand writing. We found that the low-cost and easily prepared supra-CNDs can be expected to show considerable potential to achieve multi-level encryption in anti-counterfeiting and information security.